Peran Guru PAI dalam Pendidikan Al-Qur’an pada Penyandang Disabilitas Tunanetra - Nuswa Salis Hamida; Triono Ali Mustofa (Departement of Mathematics Education, 2023)
As a holy book, every Muslim has the right to be able to access the Al-Qur'an, especially to read it, including persons with disabilities such as the visually impaired. In the teaching and learning process the role of the Islamic Religious Education teacher also fosters a love of reading the Qur'an in blind students because later blind students can also be confident to read the Qur'an. Departing from this, structured efforts are needed both theoretically and practically to protect, serve, and develop the potential of persons with disabilities. One of the paths taken is through education in a broad sense, where the ultimate goal is to eliminate stereotypes, fulfill rights and encourage the independence of the disabled group. This research is a library research (library research) using a descriptive analytical approach. This study obtained the results that the role of the Islamic Religious Education teacher was as a teacher which included planning, implementation, and evaluation. The role of the Islamic Religious Education teacher as a guide is to provide information, overcome learning difficulties, know and understand students. In providing information the teacher uses the method of reading together, lectures to explain hijaiyah letters. Overcoming student learning difficulties the teacher guides how to learn to touch properly.